O jovem como leitor e autor da própria vida: contribuições de Paul Ricoeur para o autoconhecimento e o projeto de vida no Novo Ensino Médio" - Rafael Zanata Albertini (2025)
The problem of self-knowledge and reflection on personal identity are some of the most important elements in human life. Both avoid simplification and require complex responses. This task takes on even greater meaning and challenges when considering the lives of adolescents, due to the transformation processes they go through and the concern surrounding their future. In view of this, this research aims to understand how Paul Ricoeur's philosophical work can contribute to self-knowledge and the formulation of the life project of High School students, in order to make them readers and authors of themselves. To this purpose, three steps are taken. First, a critical exposition of the formative documents that govern the New High School at the federal and state levels is made, particularly around the notion of life project that the present. Next, Ricoeur's philosophical thought on the problem of personal identity is presented, especially through one of his most notable concepts: narrative identity. Finally, an educational product is presented that aims to bring together Ricoeur's philosophical contributions to pedagogical demands. The product consists of a didactic sequence of five duplicated class meetings linked to the Life Project Curricular Unit, which can be applied to other components – especially in Philosophy classes and in the Formative Itineraries of the Humanities and Applied Social Sciences.